Improving eye-drop administration skills of patients - a multicenter parallel-group cluster-randomized controlled trial - Lampert, Anette; Bruckner, Thomas; Haefeli, Walter E.; Seidling, Hanna (PLOS ONE, 2019)
Background: Eye-drop administration errors occur in the majority of patients and increase the risk for treatment failure or systemic adverse events. While lacking knowledge is the principal error cause, most patients overestimate their skills and are unaware of often substantial knowledge gaps. Therefore, the impact of including motivational patient education on long-term eye-drop administration skills of patients was investigated. Methods: This is a cluster-randomized controlled trial in German community pharmacies. Patient education in both groups comprised observation of the patient during eye-drop administration to identify individual errors, pharmaceutical counseling, and teach-back evaluation of the training. In the intervention group, motivational communication techniques were included to increase error awareness and readiness for patient education. In addition, intervention patients were trained on repeated errors until administration was performed correctly. In contrast, patients in the control group only received feedback on erroneous administration steps without another assessment and reinforced training. Results: In total, 152 adult patients were eligible to the study and 91 patients (intervention group N = 46) agreed to participate in a 1-month, 6-month, and 12-month follow-up. Patient education significantly increased the proportion of patients correctly administering eye-drops from 6% (7 out of 56 intervention patients, 1 out of 82 control patients) at baseline to 35% (12 out of 30 intervention patients, 12 out of 39 control patients, p ≤ 0.001) at the 1-month follow-up, and 64% (11 out of 15 intervention patients, 17 out of 29 control patients, p ≤ 0.001) at the 6-month follow-up irrespective of group allocation. In some patients previously resolved errors recurred during follow-up visits. This emphasizes the need for periodical reevaluation of patient administration skills and the provision of prevention strategies besides education. Conclusion: Patient education that included demonstration of administration skills and verbal and written counseling on observed errors improved eye-drop administration skills irrespective of the communication technique applied. Whereof, high drop-out rates limited the power to detect a difference between groups. In particular, periodic demonstration of administration skills seemed important for sustainable improvement of administration skills. However, further error prevention strategies such as additional education materials or support by a caregiver may be necessary in some patients.
Gesehen am 24.07.2019